An early look at the Organ Procurement and Transplantation Network explant pathology form data. Issue 6 (June 2016) - Harper, Ann M.; Edwards, Erick; Washburn, W. Kenneth; Heimbach, Julie
Abstract : In April 2012, the Organ Procurement and Transplantation Network (OPTN) implemented an online explant pathology form for recipients of liver transplantation who received additional wait‐list priority for their diagnosis of hepatocellular carcinoma (HCC). The purpose of the form was to standardize the data being reported to the OPTN, which had been required since 2002 but were submitted to the OPTN in a variety of formats via facsimile. From April 2012 to December 2014, over 4500 explant forms were submitted, allowing for detailed analysis of the characteristics of the explanted livers. Data from the explant pathology forms were used to assess agreement with pretransplant imaging. Explant data were also used to assess the risk of recurrence. Of those with T2 priority, 55.7% were found to be stage T2 on explant. Extrahepatic spread (odds ratio [OR] = 6.8; P < 0.01), poor tumor differentiation (OR = 2.8; P < 0.01), microvascular invasion (OR = 2.6; P < 0.01), macrovascular invasion (OR = 3.2; P < 0.01), and whether the Milan stage based on the number and size of tumors on the explant form was T4 (OR = 2.4; P < 0.01) were the strongest predictors of recurrence. In conclusion, this analysis confirms earlier findings that showed an incomplete agreement between pretransplant imaging and posttransplant pathology in terms of HCC staging, though the number of patients with both no pretransplant treatment and no tumor in the explant was reduced from 20% to <1%. In addition, several factors were identified (eg, tumor burden, age, sex, region, ablative therapy, alpha‐fetoprotein, Milan stage, vascular invasion, satellite lesions, etc.) that were predictive of HCC recurrence, allowing for more targeted surveillance of high‐risk recipients. Continued evaluation of these data will help shape future guidelines or policy recommendations. Liver Transplantation 22 757–764 2016 AASLD .